An investigation into student academic help seeking behaviours in a tertiary institution's learning support centre : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate in Education at Massey University, Palmerston North, New Zealand - Protheroe, Mervyn (Massey University, 2009)
The majority of academic help seeking studies worldwide have predominantly used the quantitative paradigm and have been undertaken in the secondary and primary sector. This project addresses a perceived gap in the research as it was conducted in a tertiary institution‟s learning centre in Aotearoa, New Zealand using Constructivist Grounded Theory in order to gain a deeper understanding of tertiary students‟ academic help seeking. Help seeking theory was reconceptualised in order to provide a more descriptive model of the process, than had previously occurred because of the quantitative nature of the majority of the previous help seeking studies. Eight participants from a tertiary institute‟s learning centre were interviewed about their motivation to seek academic help; were videoed during a learning support session; and then interviewed regarding this session. Grounded theory was used to analyse the data from both interviews and the videoed learning support session. Four aspects were indentified that motivated participants to seek academic help: the recognition of the need for help; views of help seeking; participants‟ views of themselves as help seekers; and confidence. Two previously theorised types of help seeking, executive and instrumental help seeking, were confirmed in the videoed learning support sessions. Two new types were also identified, executive/instrumental and instrumental/executive help seeking, which were combinations of previously identified help seeking types. Help seeking approach was also discerned as different from help seeking type. Help seeking approach was theorised as a state that seemed to be a background against which the four help seeking types occurred. Behavioural precipitators of academic help seeking were identified as either tutor or student initiated and were further categorised as prompts, pressures, permissions and provocations. A tentative overall model of tertiary help seeking was developed. iv The findings of this study indicate that external pressures or permissions precipitated executive or instrumental help seeking, whereas external prompts precipitated executive/instrumental or instrumental/executive help seeking and provocation precipitators led to executive/instrumental, instrumental/executive or instrumental help seeking. Recommendations for practitioners include being aware of the four different help seeking types used by tertiary students, and that tutor actions can precipitate any of the four help seeking types dependent on the help seeking approach displayed by students. Recommendations also highlight that tutors need to be aware that student confidence is an important element in seeking help, and that students may not always see help seeking as positive. Suggestions for further research were outlined.
Keywords: Adult education; Learning support centre; Tertiary education; Fields of Research::330000 Education::330100 Education Studies::330101 Educational psychology